2021
DOI: 10.1016/j.mex.2021.101402
|View full text |Cite
|
Sign up to set email alerts
|

Literature review on income inequality and economic growth

Abstract: This paper provides a comprehensive literature review of the relationship between income inequality and economic growth. In the theoretical literature, we identified various models in which income inequality is linked to economic growth. They include (i) The level of economic development, (ii) The level of technological development, (iii) Social-political unrest, (iv) The savings rate, (v) The imperfection of credit markets, (vi) The political economy, (vii) Institutions and (viii) The fertility rate. Based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 61 publications
0
33
0
5
Order By: Relevance
“…There is very little existing literature on the relationship between income inequality and green development efficiency, and most of the research on income inequality is mainly conducted in terms of causes and effects on economic development, due to various factors linking income inequality and economic growth. Different conduction mechanisms have different results, that is, some are positive, some are negative, and some are uncertain (Mdingi et al, 2021).Therefore, the results of the relationship between income inequality and economic growth remain controversial. Early empirical studies have shown that income inequality has an inhibitory effect on economic growth (Alesina et al, 1994;Persson, 1994;Perotti, 1996), and many scholars have since confirmed this negative association (Panizza, 2002;Wan et al ., 2006;Royuela et al, 2019;Braun et al, 2019;Breunig et al, 2020).However, research on the negative effects of income inequality on economic growth has been challenged by positive findings, with some scholars arguing that income inequality has a positive effect on economic growth (Forbers et al, 2000;Shahbaz, 2010;Scholl et al,2019;Toni,2021).In addition, some studies have produced inconclusive results that in high-income economies, the impact of income inequality on economic growth is positive, and in low-income economies, income inequality has a negative effect of inhibiting economic growth, for example (Barro , 2000;Croix et al, 2003;Fawaz et al, 2014;Brueckner et al, 2018).…”
Section: Income Inequality and Economic Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…There is very little existing literature on the relationship between income inequality and green development efficiency, and most of the research on income inequality is mainly conducted in terms of causes and effects on economic development, due to various factors linking income inequality and economic growth. Different conduction mechanisms have different results, that is, some are positive, some are negative, and some are uncertain (Mdingi et al, 2021).Therefore, the results of the relationship between income inequality and economic growth remain controversial. Early empirical studies have shown that income inequality has an inhibitory effect on economic growth (Alesina et al, 1994;Persson, 1994;Perotti, 1996), and many scholars have since confirmed this negative association (Panizza, 2002;Wan et al ., 2006;Royuela et al, 2019;Braun et al, 2019;Breunig et al, 2020).However, research on the negative effects of income inequality on economic growth has been challenged by positive findings, with some scholars arguing that income inequality has a positive effect on economic growth (Forbers et al, 2000;Shahbaz, 2010;Scholl et al,2019;Toni,2021).In addition, some studies have produced inconclusive results that in high-income economies, the impact of income inequality on economic growth is positive, and in low-income economies, income inequality has a negative effect of inhibiting economic growth, for example (Barro , 2000;Croix et al, 2003;Fawaz et al, 2014;Brueckner et al, 2018).…”
Section: Income Inequality and Economic Growthmentioning
confidence: 99%
“…Many previous studies have done a lot of research on the pairwise relationship among the three. For example, the effect of income inequality on economic growth (Aghion et al, 1999;Acemoglu, 2002;Acemoglu, 2005;Cingano, 2014;Dabla-Norris et al, 2015;Mdingi et al, 2021), for either In the research on the relationship between the two, most scholars believe that in the period of low economic development, income inequality will promote economic growth, while with the improvement of economic development level, income inequality will hinder the development of economic growth.Secondly, the current scholars' research on the relationship between income inequality and carbon emissions is not unified. Income inequality and climate change have always been two unresolved challenges facing mankind.…”
Section: Introductionmentioning
confidence: 99%
“…Income disparity is also demonstrated to be negatively correlated with growth by political economics theories, flaws in institutions, credit market defects, and the birth rate. The savings rate theory is the only one that continues to maintain a favorable relationship between income disparity and growth (Mdingi & Ho, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…La literatura económica también ha abordado compilaciones de las conclusiones de estas investigaciones, así como análisis de su validez y explicaciones sobre la gran heterogeneidad en los resultados. Mdingi & Ho (2021) hacen una revisión de la literatura relacionada, compilan los mecanismos de transmisión y muestran de manera separada las investigaciones que encuentran efectos negativos, efectos positivos y resultados inconclusos, respectivamente. Neves & Silva (2014) hacen lo mismo y, adicionalmente, concluyen que la gran heterogeneidad en los resultados se debe a tres dimensiones que deben ser tenidas en cuenta en estas investigaciones: i) Países y periodos escogidos: las especificidades de los países o las regiones pueden influenciar los resultados de las investigaciones, por lo que se les debería dar prioridad en lugar de tratar de buscar patrones universales.…”
Section: Revisión De Literatura Internacionalunclassified